Nonword repetition and phoneme elision skills in school‐age children who do and do not stutter. Issue 6 (7th August 2013) - Sasisekaran, Jayanthi; Byrd, Courtney
Abstract: Nonword repetition and phoneme elision represent the combined influence of several speech and language processes. In the present study we investigated nonword repetition and phoneme elision performance in school‐age children who stutter (CWS) and children who do not stutter (CNS). Participants were 14 CWS (mean = 11.7 years, SD = 2.1 years) and age‐ and sex‐matched CNS (mean = 11.8 years, SD = 2.0 years). Each talker group was further subdivided into two age groups: younger ( N = 7; 8–11.5 years) and older ( N = 7; 11.6–15 years). Repeated‐measures analyses were conducted on the accuracy and response time (in seconds) data. In nonword repetition, the CWS showed a trend for lower per cent of correct phonemes at the two‐syllable level compared with the CNS. In phoneme elision, the younger CWS showed a significantly lower accuracy rate than the older CWS at the two‐ and three‐syllable nonword lengths, while similar differences were not evident between the younger versus older CNS at any of the nonword lengths. No accuracy difference in phoneme elision was noted between the two talker groups. Group differences in speech initiation times were also not evident in either of the tasks. Findings from nonword repetition offer tentative support for difficulties experienced by school‐age CWS in phonemic encoding/working memory abilities. Findings from the phoneme elision task suggest a complex pattern of age‐dependent performance by the CWS. Comparison of response accuracy and speech initiation times in both the tasks failed to show speed–accuracy trade‐off strategies in either of the groups.